Inter-class Concomitant Pharmacotherapy in Medicaid-Insured Youth Receiving Psychiatric Residential Treatment - Edelsohn, Gail A.; Eren, Kemal; Parthasarathy, Meghna; Ryan, Neal D.; Herschell, Amy (Frontiers in Psychiatry, 2021)
Background: Concomitant pharmacotherapy has become increasingly common in the treatment of youth, including in psychiatric residential treatment facilities (PRTF) despite limited efficacy and safety data. Research on the prevalence of any class and interclass concomitant pharmacotherapy, specific class combinations of psychotropics, and changes in number of medications from admission to discharge for Medicaid insured youth treated in PRTFs in one mid -Atlantic state. Methods: Medicaid administrative claims data were examined for youth under age 18 years who were discharged from one of 21 PRTFs during calendar year 2019. Descriptive statistics were calculated to examine patterns of service utilization 90 days prior to admission. The rates of concomitant psychotropic use at admission were compared to the rates at discharge. Logistic regression models were used to examine covariates associated with discharging on 4 or more medications. Results: Fifty-four % of youth were admitted on either two or three psychotropics, while 25 % were admitted on four or more psychotropics. The proportion of youth admitting and discharging on 2 or 3 medications was stable. There was a 27 % increase in number of youth discharging on 4 medications with a 24 % decrease in those on a 5- drug regimen. Only the number of medications prescribed at admission was found to be significant (p< .001), with more medications at admission contributing to probability of discharging on 4 or more medications. Conclusions: Concomitant pharmacotherapy is common in PRTFs. These findings support the practice of deprescribing and underscore the need for further research.